2015
DOI: 10.1016/j.oraloncology.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic control of expression of the immunoregulatory molecule PD-L1 in epithelial cells and squamous cell carcinoma

Abstract: Recent clinical results for PD-1 blockade therapy have demonstrated durable tumor control with minimal immune-related adverse effects. PD-L1 is induced in non-lymphoid tissue cells and tumor cells, in addition to tissue-recruiting immune cells, under inflammatory conditions triggered by several cytokines, especially IFN-γ, and exogenous stimuli delivered by pathogen-associated molecular patterns. Receptor-mediated signaling molecules that affect the cell cycle, proliferation, apoptosis, and survival (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
271
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(290 citation statements)
references
References 75 publications
13
271
1
3
Order By: Relevance
“…It might be related to the slightly worse hypoxia conditions in longer tumors, as PD-L1 is reportedly induced under hypoxia conditions [30,31]. Additionally, upstream molecules involved in PD-L1 expression may also promote cellular proliferation [27,32]. Another possible explanation is that activation of the PD-1/PD-L1 pathway may promote tumor immune escape, allowing tumor cells to proliferate and spread more rapidly [28].…”
Section: Discussionmentioning
confidence: 99%
“…It might be related to the slightly worse hypoxia conditions in longer tumors, as PD-L1 is reportedly induced under hypoxia conditions [30,31]. Additionally, upstream molecules involved in PD-L1 expression may also promote cellular proliferation [27,32]. Another possible explanation is that activation of the PD-1/PD-L1 pathway may promote tumor immune escape, allowing tumor cells to proliferate and spread more rapidly [28].…”
Section: Discussionmentioning
confidence: 99%
“…Assays of PD-L1 protein expression by immunohistochemistry are used to determine which tumors would best be treated with an anti-PD-L1 antibody, but it is an imperfect measurement practice because there is lack of standardization of methods and it can sometimes be difficult to differentiate PD-L1-positive tumor cells from the other PD-L1-positive cells in the tumor microenvironment [73] . Moreover, immunohistochemistry has a lower sensitivity compared to studies measuring PD-L1 mRNA expression [74] . Anti-PD-1 and anti-PD-L1 antibody treatments are currently the most investigated ICIs because they have shown less severe toxicity, or high-grade "immunerelated adverse effects" (irAEs), than anti-CTLA-4 antibody treatments (5-20% compared to 10-40% respectively) [75][76][77][78][79] .…”
Section: Antibodies To Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Recent preclinical studies found programmed cell death protein 1 (PD-1) overexpression in keratinocytes to be associated with accelerated SCC development (74). Immunotherapeutic agents blocking PD-1/PD-1L1 (PD-1 ligand 1) pathway are currently undergoing phase II studies in patients with locally advanced or metastatic CSCC.…”
Section: Programmed Cell Death Protein 1 Inhibitorsmentioning
confidence: 99%